Efficacy and Tolerability of Pharmacotherapy Options for the Treatment of Medullary Thyroid Cancer - Deshpande, H. A. (Libertas Academica, 2012)
Metastatic and unresectable medullary thyroid carcinoma (MTC) is often difficult to treat as it is relatively unresponsive to radiation and conventional chemotherapy. This emphasizes the importance of the development of targeted therapies for advanced MTC. Vandetanib was approved by the US Food and Drug Administration for the treatment of symptomatic or progressive MTC in patients with advanced disease in April 2011. This therapy proved to be a breakthrough in the management of MTC. We review the efficacy and safety of this novel treatment and other treatments that are being evaluated in this disease.